ARID5B regulates fatty acid metabolism and proliferation at the Pre-B cell stage during B cell development - Chalise, Jaya Prakash; Ehsani, Ali; Lemecha, Mengistu; Hung, Yu-Wen; Zhang, Guoxiang; Larson, Garrett P.; Itakura, Keiichi (Frontiers in Immunology, 2023)
During B cell development in bone marrow, large precursor B cells (large Pre-B cells) proliferate rapidly, exit the cell cycle, and differentiate into non-proliferative (quiescent) small Pre-B cells. Dysregulation of this process may result in the failure to produce functional B cells and pose a risk of leukemic transformation. Here, we report that AT rich interacting domain 5B (ARID5B), a B cell acute lymphoblastic leukemia (B-ALL) risk gene, regulates B cell development at the Pre-B stage. In both mice and humans, we observed a significant upregulation of ARID5B expression that initiates at the Pre-B stage and is maintained throughout later stages of B cell development. In mice, deletion of Arid5b in vivo and ex vivo exhibited a significant reduction in the proportion of immature B cells but an increase in large and small Pre-B cells. Arid5b inhibition ex vivo also led to an increase in proliferation of both Pre-B cell populations. Metabolic studies in mouse and human bone marrow revealed that fatty acid uptake peaked in proliferative B cells then decreased during non-proliferative stages. We showed that Arid5b ablation enhanced fatty acid uptake and oxidation in Pre-B cells. Furthermore, decreased ARID5B expression was observed in tumor cells from B-ALL patients when compared to B cells from non-leukemic individuals. In B-ALL patients, ARID5B expression below the median was associated with decreased survival particularly in subtypes originating from Pre-B cells. Collectively, our data indicated that Arid5b regulates fatty acid metabolism and proliferation of Pre-B cells in mice, and reduced expression of ARID5B in humans is a risk factor for B cell leukemia.